Ca' Granda, an avant-garde hospital between the Renaissance and Modern age: a unique scenario in European history. Issue 1 (January 2022) - Mattia, Mirko; Biehler-Gomez, Lucie; Sguazza, Emanuela; Galimberti, Paolo Maria; Vaglienti, Folco; Gibelli, Daniele; Poppa, Pasquale; Caccia, Giulia; Caccianiga, Marco; Vanin, Stefano; Manthey, Laura; Jantz, Richard L.; et al.
Abstract: The Ospedale Maggiore, known as Ca' Granda, was founded in 1456 by will of Francesco Sforza, Duke of Milan, and was considered for almost five centuries a model for Milanese, Italian and even European healthcare. Attracting patients from all over Europe, the Ca' Granda distinguished itself for the introduction of new treatments and innovative health reforms. In the burial ground of the hospital still lie the bodies of the deceased patients, who came from the poorest strata of the population. The study of their remains aims to give back a general identity and a story to each of these persons as well as reconstruct a fraction of the sixteenth century population of Milano as concerns lifestyle and disease and examine practises and therapy of this exceptional hospital. It is estimated that about two million commingled bones and articulated skeletons rest in the crypt, together with other types of findings (e.g., ceramic, coins, clothing). These remains are the object of a large project involving various disciplines ranging from humanities to hard sciences. The aim of this paper is to bring this historical gem to the attention of scholars and provide a glimpse of what its contents have already revealed.